2021
DOI: 10.7717/peerj.11471
|View full text |Cite
|
Sign up to set email alerts
|

Longer leisure walking time is associated with positive self-rated health among adults and older adults: a Brazilian nationwide study

Abstract: Background To verify the association between weekly leisure walking time and positive self-rated health in the Brazilian adult and elderly population. Methods This cross-sectional study used information collected in 2019 across all regions of Brazil. This study included 25,785 people aged ≥ 18 years (mean = 51.6; standard deviation = 18.0) from all capitals of the Brazilian states who reported practicing walking as physical activity during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The present study found that individuals who practiced leisure walking (at least 10 min) were more likely to present the recommended sleep hours when compared to those who did not. Walking is considered a type of moderate-intensity physical activity and is directly associated in previous studies with better indicators of physical and mental health in adults and older adults [32]. Systematic reviews and meta-analyses conducted in populations with and without diagnosis of diseases reported that moderate-intensity exercise is associated with adequate sleep duration [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found that individuals who practiced leisure walking (at least 10 min) were more likely to present the recommended sleep hours when compared to those who did not. Walking is considered a type of moderate-intensity physical activity and is directly associated in previous studies with better indicators of physical and mental health in adults and older adults [32]. Systematic reviews and meta-analyses conducted in populations with and without diagnosis of diseases reported that moderate-intensity exercise is associated with adequate sleep duration [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as genetics has little influence on sleep quality, it is believed that environmental aspects such as lifestyle, for example, may explain these differences. As PA is an aspect of lifestyle and males practice more PA than females [32][33][34], it is suggested that PA may be a possible explanation for this difference between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated other lifestyle behaviors as correlates, including self-reported leisure-time physical activity (< 150 min/week versus ≥150 min/week, according to the current guidelines from the World Health Organization [ 6 ]), consumption of sugary foods and soft drinks (both classified as < 5 days/week versus ≥5 days/week, based on the frequent consumption [ 25 ]). Finally, health status factors, comprising elevated depressive symptoms (defined as a score > 9 in the Patient Health Questionnaire-9 [ 26 ]), obesity (defined as a body mass index ≥30 kg/m 2 [ 27 ]), and self-rated health (good/bad [ 28 ]) were also investigated as screen time correlates.…”
Section: Methodsmentioning
confidence: 99%
“…According to the above definition, it is hard to determine whether physical activities in leisure time should be considered as physical activities or leisure activities. To further clarify the term of leisure activity, some scholars have defined it as 'leisure-time non-exercise activities', including gardening work, raising domestic animals, reading books or newspaper, playing cards et al [10] [12] [16]. Prior studies have documented the importance of participating in leisure activities in promoting older adults' health.…”
Section: Introductionmentioning
confidence: 99%